2022
DOI: 10.3389/fphy.2022.770536
|View full text |Cite
|
Sign up to set email alerts
|

Optical measurement of an impact reaction in a modeled wing

Abstract: In this research, an impact reaction which was provoked far from its origins was studied. A metal box filled with sand was used to emulate a rigid body in which a steel bar was embedded; these conditions simulated the fuselage and wing, respectively, and the impact was applied to the rigid body and the measurement to the bar. For this, an optical technique was used to measure the relative displacement of the steel bar, and the measurements are obtained by applying digital image correlation; 2D images were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Finally, the authors reported another solution for a damped oscillator, in which they showed a combination of harmonic and linear functions [9]. In comparison with these studies, the present article demonstrates that the analytical results reproduced the experimental motion in every array.…”
Section: Analytical Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Finally, the authors reported another solution for a damped oscillator, in which they showed a combination of harmonic and linear functions [9]. In comparison with these studies, the present article demonstrates that the analytical results reproduced the experimental motion in every array.…”
Section: Analytical Discussionsupporting
confidence: 70%
“…According to the analytical solutions shown in [7][8][9], first, the authors declared a sum of two waves as the first analytical approximation to the motion recorded experimentally. This solution gave them an accuracy of 92%.…”
Section: Analytical Discussionmentioning
confidence: 99%
See 3 more Smart Citations